Gadolin's problem on the assembly of a two-layer shaft by a shrink fit with a test of the connection for separation - Anatoly A. Burenin; Anastasia V. Tkacheva; Sergey Viktorovich Firsov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2022)
The connection strength in the interference fit assembly of a two-layer shaft produced by the shrink fit operation is studied. The materials of the assembly parts are considered to be ideal elastoplastic, with yield stregth that are significantly depended on temperature. In the calculations, the conditions of plane deformed states are taken into account. Pull tests are performed by rotating the assembly around its axis, when pulling forces are generated in the form of centrifugal forces of inertia. It is shown that with an increase of the rotation speed, the tightness in the assemblies is decreased. Limitations of the possible angular speed are calculated under the assembly tightness disappearing.